Relación diámetro - altura total - amplitud de copa de las plantas de Swietenia macrophylla King "caoba" con diferentes dosis de fertilización foliar en plantación. Puerto Almendra, Loreto, Perú - 2021 - García Reyna, Franco Renato (2022)
The study was carried out in a plantation belonging to CIEFOR Puerto Almendra – FCF - UNAP, San Juan Bautista, Maynas, Loreto, Peru. The objective was to determine the degree of relationship between diameter, total height and crown width in Swietenia macrophylla King "caoba" plants with different doses of foliar fertilization in plantation, Puerto Almendra, Loreto, Peru - 2021. The variables were diameter, total height and crown width of the evaluated plants. The results obtained show that in this study the relationships between the 3 variables used for doses 1 and 3, the degree of relationship between these variables is excellent; the best fit allometric model for Swietenia macrophylla King “caoba” was cubic in doses 1 – 2 and for dose 3 they were compound, cubic and power; the relationship affinity between the 3 variables was 55% to 96%.